Microbial community structure characteristics among different karst aquifer systems, and its potential role in modifying hydraulic properties of karst aquifers - Liang, Zuobing; Li, Shaoheng; Wang, Zhuowei; Li, Rui; Yang, Zhigang; Chen, Jianyao; Gao, Lei; Sun, Yuchuan (Frontiers in Microbiology, 2023)
Little is known about how microbial activity affects the hydraulic properties of karst aquifers. To explore the potential impacts of microbial activity on the hydraulic properties of karst aquifers, microbiological analysis, heat tracer, isotope (dissolved inorganic carbon isotope, δ13CDIC) and aqueous geochemical analyses were conducted at six monitoring wells in Northern Guangdong Province, China. Greater hydraulic conductivity corresponded to a low temperature gradient to an extent; the temperature gradient in karst groundwater aquifers can reflect the degree of dissolution in wells. Higher HCO3- concentrations coupled with lower d-excess and pH values at wells B2 and B6 reflect potential microbial activity (e.g., Sulfuricurvum kujiense) causing carbonate dissolution. Microbial activity or the input of anthropogenic acids, as evidenced by significantly more positive δ13CDIC values, potentially affect carbonate dissolution in deep karst aquifers, which eventually alters hydraulic conductivity. However, more direct evidence is needed to quantify the effects of microbial activity on carbonate dissolution in karst aquifers.